2021
DOI: 10.1002/jgf2.462
|View full text |Cite
|
Sign up to set email alerts
|

Changes in influenza vaccination coverage associated during the COVID‐19 pandemic in Japan

Abstract: Changes in influenza vaccination coverage during the COVID‐19 pandemic in Japan were limited. Not only changes in individual behavior and the threat of disease, but also vaccine dissemination policy based on system‐based interventions, including behavioral economic approaches, is desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Third, we could not collect vaccine-related information, which is strongly associated with influenza infection status. In Japan, the influenza vaccination rate has been approximately 40% in recent years [ 38 ]. A previous meta-analysis showed that adults with obesity are more likely to receive influenza vaccination [ 39 ], suggesting an underestimation of the association between visceral fat and influenza infection.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we could not collect vaccine-related information, which is strongly associated with influenza infection status. In Japan, the influenza vaccination rate has been approximately 40% in recent years [ 38 ]. A previous meta-analysis showed that adults with obesity are more likely to receive influenza vaccination [ 39 ], suggesting an underestimation of the association between visceral fat and influenza infection.…”
Section: Discussionmentioning
confidence: 99%